2021
DOI: 10.1080/02687038.2021.1907295
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of narrative discourse in post-stroke aphasia

Abstract: Background: Previous findings have demonstrated the importance of discourse analysis in post-stroke aphasia, as it allows for in-depth examination of language impairment and represents key components of functional communication.However, little is known about the recovery of discourse over time. Aims:The main aim of this study is to measure the longitudinal changes in descriptive discourse production from the acute to chronic stages of post-stroke aphasia recovery. The secondary aim is to explore the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…Briefly, we demonstrated that the TUs score in picture description is sensitive to language impairment and appears related to overall language measure (i.e. a composite score composed of lexico-semantic, comprehension and repetition tasks; García et al, 2020) in both acute and chronic stages of recovery in post-stroke aphasia (Brisebois et al, 2020(Brisebois et al, , 2021. Conversely, very few microstructural variables showed the same qualities.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Briefly, we demonstrated that the TUs score in picture description is sensitive to language impairment and appears related to overall language measure (i.e. a composite score composed of lexico-semantic, comprehension and repetition tasks; García et al, 2020) in both acute and chronic stages of recovery in post-stroke aphasia (Brisebois et al, 2020(Brisebois et al, , 2021. Conversely, very few microstructural variables showed the same qualities.…”
Section: Introductionmentioning
confidence: 84%
“…We expected similar results across the two modalities based on previous findings (Georgeadis et al, 2004;Turkstra et al, 2012). Second, it aimed to continue the exploration of the TUs checklist that we have recently developed (Brisebois et al, , 2021. We expected that each TUs would be produced by a similar proportion of participants in both the in-person group and videoconference group.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Collecting multiple discourse tasks (e.g., personal narrative, story retell or picture description) is essential to reveal discourse competencies in post-stroke patients because it allows for a better representation of actual language use (Brookshire & Nicholas, 1994). Still, most studies investigating discourse, including ours (Brisebois et al, 2020(Brisebois et al, , 2022, report only one type of task (Bryant et al, 2016), which may provide an incomplete profile of the individuals' discourse processing skills (Sherratt & Bryan, 2019).…”
Section: Assessing Multiple Tasks In Discourse Analysismentioning
confidence: 99%